Faktor-faktor yang Mempengaruhi Pengalokasian Belanja Daerah pada Provinsi Riau Tahun 2017-2021 - Yois Nelsari Malau; Iis Dahlia Silitonga; Riris Jesica Silaban; Nisa Hasugian; Belthasar Trito Siahaan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of the following research is to find out the real impact of SAF, ROR, PSF, GAF and inflation on regional spending. The population and sample are 12 districts/cities from 2017-2021, using a saturated sampling technique. The coefficient of determination is 0.953, which is 95.3% for SAF, ROR, PSF and inflation in regional spending and 4.7% for other independent variables. The results of the discussion indicate that actually SAF, ROR, PSF, and GAF have separate impacts, but inflation has a negative impact on regional spending. SAF, ROR, PSF, GAF and inflation in their entirety had an impact on Regional Expenditures